(untitled) (Global Journals of Research in Engineering, 2019)
Vacuum Assisted Climbing Device is a new way to climb vertical surfaces like wall buildings easily and faster than the conventional methods like ladders and ropes etc This device works on the vacuum to climb the vertical surfaces as its name indicate and this vacuum is utilized by two suction pads which are available in the hands of the climber and the suction pads are connected with the suction motor vacuum pump with the hoses